A training needs analysis of admiral nurses to facilitate advance care planning in dementia. (June 2019) - Harrison Dening, Karen; Scates, Caroline; McGill, George; De-Vries, Kay
Education of health and social care professionals is essential in preparation to confidently and effectively support families affected by dementia to undertake advance care planning. This article describes a training needs analysis of Admiral Nurses, dementia specialists, in facilitating advance care planning for future care. Methods: A questionnaire survey was completed by Admiral Nurses attending end-of-life care masterclasses in 2017 and 2018. Both quantitative (years registered as a nurse, years as an Admiral Nurse and subjective level of confidence in completing advance care plannings) and qualitative data (interventions perceived to increase confidence) were collected. Findings: There were 75 completed responses (two incomplete returns). There was no correlation between levels of confidence and years registered as a nurse. However, there was a small positive correlation between confidence and number of years as an Admiral Nurse ( r = 0.23; p < 0.05). Themes identified qualitatively to enhance practice were advanced communication skills, supervised practice, resources to frame conversations and a guide and template for advance care planning. Conclusion: Although Admiral Nurses are specialists in dementia, several educational initiatives could be employed to better enable them to support advance care planning for families affected by dementia. This training needs analysis is contributed towards developing an educational intervention for Admiral Nurses to improve advance care planning support.